THE EFFECT OF RETURN ON ASSET (ROA) AND NET PROFIT MARGIN (NPM) ON PROFIT GROWTH IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2021-2023 PERIOD - Sanju Imanuel Silaen; Herlin Munthe; Maduma Sari Sagala (ZILLZELL MEDIA PRIMA, 2025)
The purpose of this study is to assess how Return on Assets (ROA) and Net Profit Margin (NPM) affect profit growth. A quantitative method was used in conducting this study, with a focus on secondary data collection. The research population includes manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period from 2021 to 2023. A total of 126 companies were selected as samples, and the list of these companies can be accessed through the official IDX website at www.idx.co.id. The data were processed and analyzed using SPSS version 23, applying multiple linear regression analysis techniques to determine the effect of ROA and NPM on profit growth. The results of the analysis indicate that individually, both ROA and NPM do not have a statistically significant effect on profit growth. However, when the variables are examined simultaneously, the study finds that they have a significant combined influence on the increase in company revenue, suggesting the importance of analyzing financial indicators together rather than in isolation.